Lessons from the Sweetpotato Seed System and Crop Management Community of Practice - International Potato Center (2018)
This brief describes the establishment and evolution of a sweetpotato seed systems community of practice (CoP) and aims to identify potential lessons which could enhance the learning in other communities of practice, in particular the CGIAR Research Program on Roots, Tubers and Bananas (RTB) cross-cutting cluster on Access to Quality Seed and Improved Varieties.